Phylogenetic diversity of Amazonian tree communities. Issue 11 (21st July 2015) - Honorio Coronado, Eurídice N.; Dexter, Kyle G.; Pennington, R. Toby; Chave, Jérôme; Lewis, Simon L.; Alexiades, Miguel N.; Alvarez, Esteban; Alves de Oliveira, Atila; Amaral, Iêda L.; Araujo‐Murakami, Alejandro; Arets, Eric J. M. M.; Aymard, Gerardo A.; et al.
Abstract Aim To examine variation in the phylogenetic diversity (PD) of tree communities across geographical and environmental gradients in Amazonia. Location Two hundred and eighty‐three c. 1 ha forest inventory plots from across Amazonia. Methods We evaluated PD as the total phylogenetic branch length across species in each plot (PDss), the mean pairwise phylogenetic distance between species (MPD), the mean nearest taxon distance (MNTD) and their equivalents standardized for species richness (ses.PDss, ses.MPD, ses.MNTD). We compared PD of tree communities growing (1) on substrates of varying geological age; and (2) in environments with varying ecophysiological barriers to growth and survival. Results PDss is strongly positively correlated with species richness (SR), whereas MNTD has a negative correlation. Communities on geologically young‐ and intermediate‐aged substrates (western and central Amazonia respectively) have the highest SR, and therefore the highest PDss and the lowest MNTD. We find that the youngest and oldest substrates (the latter on the Brazilian and Guiana Shields) have the highest ses.PDss and ses.MNTD. MPD and ses.MPD are strongly correlated with how evenly taxa are distributed among the three principal angiosperm clades and are both highest in western Amazonia. Meanwhile, seasonally dry tropical forest (SDTF) and forests on white sands have low PD, as evaluated by any metric. Main conclusions High ses.PDss and ses.MNTD reflect greater lineage diversity in communities. We suggest that high ses.PDss and ses.MNTD in western Amazonia results from its favourable, easy‐to‐colonize environment, whereas high values in the Brazilian and Guianan Shields may be due to accumulation of lineages over a longer period of time. White‐sand forests and SDTF are dominated by close relatives from fewer lineages, perhaps reflecting ecophysiological barriers that are difficult to surmount evolutionarily. Because MPD and ses.MPD do not reflect lineage diversity per se, we suggest that PDss, ses.PDss and ses.MNTD may be the most useful diversity metrics for setting large‐scale conservation priorities.